Deciphering the role of coumarin as a novel quorum sensing inhibitor suppressing virulence phenotypes in bacterial pathogens - Gutiérrez-Barranquero, J.; Reen, F.; McCarthy, R.; Dobson, A.; O'Gara, Fergal (Springer Verlag, 2015)
© 2015, Springer-Verlag Berlin Heidelberg. The rapid unchecked rise in antibiotic resistance over the last few decades has led to an increased focus on the need for alternative therapeutic strategies for the treatment and clinical management of microbial infections. In particular, small molecules that can suppress microbial virulence systems independent of any impact on growth are receiving increased attention. Quorum sensing (QS) is a cell-to-cell signalling communication system that controls the virulence behaviour of a broad spectrum of bacterial pathogens. QS systems have been proposed as an effective target, particularly as they control biofilm formation in pathogens, a key driver of antibiotic ineffectiveness. In this study, we identified coumarin, a natural plant phenolic compound, as a novel QS inhibitor, with potent anti-virulence activity in a broad spectrum of pathogens. Using a range of biosensor systems, coumarin was active against short, medium and long chain N-acyl-homoserine lactones, independent of any effect on growth. To determine if this suppression was linked to anti-virulence activity, key virulence systems were studied in the nosocomial pathogen Pseudomonas aeruginosa. Consistent with suppression of QS, coumarin inhibited biofilm, the production of phenazines and swarming motility in this organism potentially linked to reduced expression of the rhlI and pqsA quorum sensing genes. Furthermore, coumarin significantly inhibited biofilm formation and protease activity in other bacterial pathogens and inhibited bioluminescence in Aliivibrio fischeri. In light of these findings, coumarin would appear to have potential as a novel quorum sensing inhibitor with a broad spectrum of action.